2012
DOI: 10.1166/jnn.2012.5129
|View full text |Cite
|
Sign up to set email alerts
|

The Stability and Optical Gap of Zinc Oxide Clusters (ZnO)<SUB><I>n</I></SUB> (<I>n</I> = 2–18)

Abstract: The stability and the optical band gap of the Zinc Oxide clusters (ZnO)n (n = 2-18) are investigated by using density functional theory (DFT) and the time-dependent density functional theory (TD-DFT), respectively. The differences between the HOMO-LUMO gap (delta(h-l)) and the optical gap (delta(opt)) are dramatic for small clusters (2 < or = n < or = 5). As the increasing of the cluster size, the differences become small. The results indicate that the stability and the optical gap are related to the sizes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…For the (ZnO) n (n = 3-5), the obtained results are in good agreement with the previous theoretical studies (Wang et al 2007;Zhao et al 2012;Chen et al 2016). The global minimum for small (ZnO) n clusters (n = 2-5) are shown to be the planar rings.…”
Section: Global Minimum Of (Zno) N (N = 3-6)supporting
confidence: 90%
See 1 more Smart Citation
“…For the (ZnO) n (n = 3-5), the obtained results are in good agreement with the previous theoretical studies (Wang et al 2007;Zhao et al 2012;Chen et al 2016). The global minimum for small (ZnO) n clusters (n = 2-5) are shown to be the planar rings.…”
Section: Global Minimum Of (Zno) N (N = 3-6)supporting
confidence: 90%
“…After changing from the Rigid ion Model to the Shell Model, the planar ring has the higher energy than the tube and two other 3D structures. The study performed by Zhao who optimized the cluster structures using the GGA-PBE level of theory along with a complete basis set of 6-311 g (d) has also predicted the "tube-like" structure to be the most stable structure of (ZnO) 6 (Zhao et al 2012). Recently, Chen et al (2016) reported the global geometry optimization of (ZnO) n clusters using an evolutionary hybrid genetic algorithm (HGA).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Castañeda, L. can prepared the ZnO nanocages which suitable for gas sensors by simple experimental technique [48]. Recently, theoretical calculation have been explored the geometric structure and electronic properties of (ZnO) n cluster with various sizes [104,[124][125][126][127][128]. Many researchers founded that (ZnO) 12 as ZnOSL is more favorable phase than other ZnO polymorphs [128][129][130].…”
Section: Introductionmentioning
confidence: 99%